Entre práticas e controle: o círculo operário e os trabalhadores de Uberlândia (1942-1960) - Pereira, Gustavo Zuquetto (2014)
This work consists of a discussion on the role of the Catholic Worker Uberlândia Circle between the years 1960 1942e. We seek to discuss relations between the workers and the local business community in order to understand the social dynamics of these groups and the politics of workers \' control through the Circle.